Delineation of Genotype × Environment Interaction for Identification of Stable Genotypes to Grain Yield in Mungbean - Samyuktha, Santhi Madhavan; Malarvizhi, Devarajan; Karthikeyan, Adhimoolam; Dhasarathan, Manickam; Hemavathy, Arumugam Thanga; Vanniarajan, Chocklingam; Sheela, Venugopal; Hepziba, Sundarrajan Juliet; Pandiyan, Muthaiyan; Senthil, Natesan (Frontiers in Agronomy, 2020)
In the present study, fifty-two mungbean (Vigna radiata) genotypes were evaluated for seven morphological traits at three different environments in South Indian state Tamil Nadu, namely Virinjipuram (E1), Echangkottai (E2), and Bhavanisagar (E3) during Kharif 2017, 2018 and 2019, respectively. The data collected were subjected to variability and correlation analyses, followed by stability analysis using additive main effects and multiplicative interaction (AMMI) model, genotype × environment interaction effects (GGE) biplot. Variablility was observed among the genotypes for the following traits viz., plant height, days to fifty per cent flowering, number of pods per plant, pod length, number of seeds per pod, hundred seed weight and grain yield. Correlation analysis showed that the trait number of pods per plant was significantly associated with grain yield. The G×E was smaller than the genetic variation of grain yield as it portrayed the maximum contribution of genotypic effects (61.07%). GGE biplot showed E3 as a highly discriminating and representative environment. It also identified environment-specific genotypes viz., EC 396111 for E1, EC 396125 for E2 and EC 396101 for E3 environments. The genotypes with minimum genotype stability index (GSI) viz., V2802BG (7), HG 22 (13), and EC 396098 (13) were observed with wide adaptation and high yields across all the three environments. In summary, we identified stable genotypes adapted across environments for grain yield. These genotypes can be used as parent/pre-breeding materials in future mungbean breeding programs.